DapBCH: a disease association prediction model Based on Cross-species and Heterogeneous graph embedding - Shi, Wanqi; Feng, Hailin; Li, Jian; Liu, Tongcun; Liu, Zhe (Frontiers in Genetics, 2023)
The study of comorbidity can provide new insights into the pathogenesis of the disease, and has important economic significance in clinical evaluation of treatment difficulty, medical expenses, length of stay and prognosis of the disease. In this paper, we propose a disease association prediction model DapBCH, which constructs a cross-species biological network and applies heterogeneous graph embedding to predict disease association. Firstly, we combine the human disease-gene network, mice gene-phenotype network, human-mice homologous gene network, and human protein-protein interaction network to reconstruct a heterogeneous biological network. Secondly, we apply heterogeneous graph embedding based on meta-path aggregation to generate the feature vector of disease nodes. Finally, we employ link prediction to obtain the similarity of disease pairs. The experimental results indicate that our model is highly competitive in predicting disease association, and is promising for finding potential disease associations.